A Survey on Nutrition Related Issues by AVRDC - World Vegetable Center (International Food Policy Research Institute, 2014)
AVRDC conducted a survey on nutrition related issues, which was planned jointly with ICRISAT. While AVRDC will make the detailed results available as appropriate, the following indications are important for the future development of these research activities; The survey found that women who were participating, or had participated (Year 1) in the Nutrition Field Schools had a much better understanding of mal-nutrition, as well food groups, and food requirements to avoid malnutrition. There appear to be some differences in the recipes on preparing children?s porridges between villages that had training, and those that had not, however, the study was conducted while the training was still going, and so the participants had not fully covered all the topics. The final results of this study will guide further detailed studies. Project title: Sustainable Intensification of Key Farming Systems in the Sudano-Sahelian Zone of West Africa. Project abstract: As part of the Feed the Future Initiative, the United States Agency for International Development (USAID) is supporting an innovative multi-stakeholder agricultural research program, the Africa Research in Sustainable Intensification for the Next Generation (Africa RISING). The program?s main objective is to identify and validate scalable options for the sustainable intensification of key African cereal-based farming systems to increase food production and improve the livelihoods of smallholder farmers and at the same time conserve or improve the natural resource base. Project website: http://africa-rising.net